ART OF STAGECRAFT reflections on design and creation in theatre. - DeCelle, F. Randy; DeCelle, Edmond Carl, 1889-1972 ([S.l.] : FOCAL PRESS, 2024)
The Art of Stagecraft: Reflections on Design and Creation in Theatre is a thoughtful examination of the intersection of design, art, and the modern and contemporary theatrical design practitioner. Utilizing a recently discovered folio of materials of stagecraft practices that was being compiled by Mobile, Alabama artist Edmond Carl deCelle, who was nationally known for his sketches, paintings, murals, Mardi Gras pageants and parades, and theatre productions along the Gulf Coast in the years 1930-1970, the book examines methodologies of production using sketches from the artist as well as his thoughts on design, art, and the shifts that were happening in the industry during the time. The book looks at a sampling of traditional theatrical design and stagecraft practices that became formalized in the mid-20th century and compares them to contemporary practices, offering a reflection on the current state of theatre production, stagecraft practices, and the theatre practitioner as an artist. For those just coming into theatre production, The Art of Stagecraft provides a resource for a selection of well-proven, straightforward techniques that have been developed over many years. For those in theatre production, the book serves as a guide for an assortment of traditional techniques that are still in use today but may not be known by everyone. For all readers, this book will also look at a sample of traditional techniques that have been phased out in favor of contemporary methods due to the development of modern materials.
Keywords: PERFORMING ARTS / Theater / Stagecraft; PERFORMING ARTS / Theater / History & Criticism; DeCelle, Edmond Carl, -- 1889-1972.; Set designers -- United States -- Biography; Theaters -- Stage-setting and scenery -- United States -- History -- 20th century